Pusa Rakshit (DTPH-60) : New promising tomato hybrid for cultivation under protected conditions - Yadav, R K; Tomar, B S; Chaudhary, H; Husain, Zakir; Singh, P K; Jat, Gograj Singh; Sumanlata, Sumanlata (Indian Horticulture, 2021)
The development of tomato hybrid for protected conditions by public sector will not only ensure off-season availability, increase in the productivity and quality, but also make available the hybrid seeds at cheaper rate to the farmers. The newly developed tomato hybrids Pusa Rakshit (DTPH-60) has thick pericarp, attractive red colour, uniform round fruit and high yielding ability.